A method for preparing carbon-coated aluminum foil for sodium ion battery

By utilizing the rough structure of the aluminum foil surface and the adhesive gel properties of sodium alginate in sodium-ion batteries, the bonding force between the coating and the aluminum foil is improved, which solves the problem of insufficient bonding ability between the aluminum foil and the coating in the existing technology and achieves Stable battery performance and improved service life.

CN116706085BActive Publication Date: 2025-01-17ZHEJIANG DINGHAO NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310527366.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-11
Publication Date
2025-01-17
Estimated Expiration
2043-05-11

AI Technical Summary

Technical Problem

In existing sodium ion batteries, the bonding ability of aluminum foil and coating is limited, resulting in the expansion of the coating and aluminum foil during the continuous charging and discharge of the battery, increasing internal resistance and reducing battery performance.

Method used

By utilizing the rough structure on the surface of the aluminum foil and the adhesive gel properties of sodium alginate, the bonding force between the coating and the aluminum foil is improved. Specific steps include: dissolving sodium ethoxide and alginic acid in absolute ethanol to form a suspension slurry; rolling the suspension slurry on the surface of the aluminum foil and drying; adding conductive carbon black and wetting and dispersing agents to form a conductive slurry. Carry out secondary roller coating and rolling treatment to enhance the bonding effect.

Benefits of technology

It effectively improves the bonding force between the coating and the aluminum foil, ensures the stability of battery performance, reduces the resistance of the pole piece, and increases the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004223194500000101
    Figure BDA0004223194500000101
  • Figure BDA0004223194500000111
    Figure BDA0004223194500000111
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a method for preparing a carbon-coated aluminum foil for sodium ion batteries. The carbon-coated aluminum foil prepared by the method comprises an aluminum foil, a coating coated on the surface of the aluminum foil, and a sodium-based adhesive material between the aluminum foil and the coating, and provides a specific preparation method. The present invention solves the adhesion problem between the existing aluminum foil and the coating, and utilizes the rough structure of the aluminum foil surface in combination with the adhesive gel property of sodium alginate to enhance the bonding force between the coating and the aluminum foil, thereby ensuring the stability of battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and particularly relates to a method for preparing a carbon-coated aluminum foil for a sodium ion battery. Background Art

[0002] Lithium-ion batteries have become ideal energy storage devices because of their advantages such as high operating voltage platform, good rate performance, long service life, high energy storage density and low self-discharge rate. However, with the shortage of lithium resources, uneven distribution and high cost, the application and promotion of lithium-ion batteries has been greatly affected.

[0003] Compared with the shortage of lithium resources, sodium not only has similar physical and chemical properties to lithium, but also has thousands of times more abundant resources in the earth's crust than lithium, and is low-cost. Therefore, sodium-ion batteries have become an excellent choice to replace lithium-ion batteries. In sodium-ion batteries, since sodium does not react with aluminum, aluminum foil is used as the current collector material, and a layer of active material is formed on the surface of the aluminum foil to form a carbon-coated aluminum foil to improve current collection. However, the bonding ability between the aluminum foil and the coating in the carbon-coated aluminum foil is limited. During the continuous charge and discharge process of the battery, the expansion of the coating and the aluminum foil is separated, resulting in an increase in internal resistance and a decrease in battery performance. Summary of the invention

[0004] In view of the problems in the prior art, the present invention provides a method for preparing a carbon-coated aluminum foil for a sodium ion battery, which solves the adhesion problem between the existing aluminum foil and the coating. The rough structure of the aluminum foil surface is combined with the adhesive gel properties of sodium alginate to improve the bonding strength between the coating and the aluminum foil, thereby ensuring the stability of the battery performance.

[0005] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0006] A method for preparing a carbon-coated aluminum foil for a sodium ion battery. The carbon-coated aluminum foil comprises an aluminum foil, a coating coated on the surface of the aluminum foil, and a sodium-based adhesive material located between the aluminum foil and the coating.

[0007] The coating is a carbon black conductive coating, and the sodium adhesive material is sodium alginate.

[0008] Furthermore, the method for preparing the carbon-coated aluminum foil for sodium ion battery comprises the following steps:

[0009] Step 1, dissolving sodium ethoxide and alginic acid in anhydrous ethanol, stirring and dispersing to form a suspension slurry; the mass ratio of sodium ethoxide to sodium alginate is 1:1.1-1.3, the concentration of alginic acid in anhydrous ethanol is 5-10g / L, and the stirring speed is 50-100r / min; in the step, sodium ethoxide has good solubility in ethanol, while alginic acid has no solubility in ethanol, therefore, putting the two into anhydrous ethanol can form a suspension, and the sodium ethoxide is evenly distributed on the surface of the alginate; at this time, the sodium ethoxide uses anhydrous ethanol as a solvent, and can maintain a certain stability;

[0010] Step 2, adding a wetting dispersant to distilled water and stirring evenly until the wetting dispersant is completely dissolved in the distilled water, then adding conductive carbon black and continuing to stir to form a homogeneous conductive slurry, wherein the wetting dispersant adopts a BYK acrylate copolymer ammonium salt solution wetting dispersant, the concentration of the wetting dispersant in distilled water is 1-2g / L, the concentration of the conductive carbon black is 100-400g / L, the stirring speed is 100-200r / min, and the temperature is 20-30°C; the wetting dispersant in this step can form a good dispersion system in water, and the conductive carbon black is added in its completely dissolved state to improve the dispersibility of the conductive carbon black and alleviate the self-agglomeration problem of the conductive carbon black;

[0011] Step 3: Roll-coat the suspension slurry on the surface of the aluminum foil and dry it in a dry environment, then roll-coat the conductive slurry for a second time, let it stand and dry to obtain the coated aluminum foil. The roll-coating amount of the suspension slurry is 20-50 μL / m 2 The drying temperature is 70-80°C, and the secondary coating amount is 1-2g / m 2 , standing and drying at 50-70°C; in this step, the suspension slurry is fixed on the surface of the aluminum foil in a dry environment, and the ethanol is evaporated and removed in a dry environment, and the conductive slurry is fixed on the dry surface of the suspension slurry by a secondary rolling coating method. In this process, the sodium ethoxide in the suspension slurry reacts with the distilled water of the conductive slurry to promote the conversion of the sodium ethoxide into sodium hydroxide. The sodium hydroxide can not only corrode the aluminum foil, increase the surface roughness of the aluminum foil, and achieve the effect of adhesion on the surface of the aluminum foil, but also react with alginic acid to form sodium alginate, and the alginic acid is slightly excessive to the sodium ethoxide, which can effectively solve the problem of excessive sodium hydroxide; sodium alginate has excellent adhesion, and can fix the conductive carbon black on the sodium alginate to form a carbon layer for fixation;

[0012] Step 4, rolling the coated aluminum foil to obtain carbon-coated aluminum foil, wherein the rolling pressure is 50-70T, the rolling speed is 20-30m / min, and the temperature is 80-90°C. During the constant temperature rolling process, the coating layer on the surface of the aluminum foil is subjected to external pressure, which improves the penetration of the conductive carbon black into the coating layer, improves the tight structure of the carbon-coated layer and the aluminum foil, and enhances the adhesion between the two. At the same time, sodium alginate itself is an adhesive gel. During the rolling process, it forms an interlaced penetration with the conductive layer formed by carbon black, which improves the adhesion of the carbon black material itself and also improves the adhesion between the coating and the aluminum foil.

[0013] The carbon-coated aluminum foil prepared by the present technical solution uses sodium alginate as an adhesive layer to form a stable adhesive effect. At the same time, sodium alginate can form an anionic gel layer on the surface to regulate the interface reaction between the negative electrode and the electrolyte, ensure the deposition of sodium ions on the surface of the negative electrode, and repel anions in the electrolyte to inhibit the generation of interface side reactions, thereby protecting the aluminum foil. Sodium alginate carries sodium ions and can play a certain role in sodium ion supplementation. In addition, the present technical solution uses sodium ethoxide to form sodium hydroxide in an aqueous environment to convert alginate into sodium alginate in situ, which can form a high-quality fit with the alkaline-corroded surface of the aluminum foil without the problem of surface bubbles.

[0014] Furthermore, the aluminum foil needs to be pre-treated before use, and the pre-treatment uses an ethanol aqueous solution as a grease cleaning agent to remove grease on the surface of the aluminum foil and clean the surface of the aluminum foil. At the same time, surface micro-corrosion is formed by acid washing and alkali corrosion, and the micro-corrosion can effectively increase the contact area of ​​the suspended slurry on the surface of the aluminum foil, thereby achieving the effect of improving the initial adhesion; at the same time, the micro-corrosion structure of the aluminum foil pre-treatment can reduce the corrosion requirements of sodium ethanol on the aluminum foil and increase the controllability of the entire system; the pre-treatment steps include: a1, using an ethanol aqueous solution to soak and clean the aluminum foil, and drying to obtain an aluminum foil with a clean surface, the ethanol volume concentration of the ethanol aqueous solution is 40-50%, and the drying temperature is 80-90°C; a2, rolling dilute hydrochloric acid and dilute alkali solution on the surface of the clean aluminum foil in turn, rinsing and drying to obtain an aluminum foil with a slightly rough surface, the pH of the dilute hydrochloric acid is 6-6.5, and the pH of the dilute alkali solution is 7.5-8. This pretreatment removes grease through ethanol-water solution to clean the surface of the aluminum foil, removes oxides on the surface of the aluminum foil with dilute hydrochloric acid, and micro-corrodes the surface with dilute alkali solution to improve the rough structure of the aluminum foil surface, which helps the adhesion of the coating material and improves the bonding strength between the aluminum foil and the coating.

[0015] Furthermore, the sodium ethoxide in step 1 can be rapidly hydrolyzed to produce sodium hydroxide, and sodium hydroxide has an effect on the formation of alginic acid. In the national standard, the water content in anhydrous ethanol is not more than 0.8%, generally 99.5%. The water content of the anhydrous ethanol still causes the sodium ethoxide to deteriorate in the dilute ethanol solution of sodium ethoxide. To solve this problem, the anhydrous ethanol is soaked in vermiculite particles and stirred evenly for 5-10 minutes before use, and then the vermiculite particles are used as filter materials for solid-liquid separation to obtain water-free ethanol. The stirring speed is 100-200r / min, and the vermiculite particles are spherical particles with a particle size of 5-10mm; the vermiculite particles themselves have good water absorption and can quickly adsorb water molecules in ethanol. At the same time, when vermiculite particles are used as filter materials, the solid splitting property of the vermiculite particles is used to quickly split the anhydrous ethanol into fine liquid streams, thereby achieving a good water molecule removal effect;

[0016] Furthermore, the alginate in step 1 is insoluble in anhydrous ethanol, and its particle size seriously affects the homogeneous dispersion of alginate in the solution. Therefore, the alginate needs to be crushed before use, and the alginate is crushed into fine particles by crushing. The alginate crushing step includes: b1, adding alginate to distilled water and stirring at a constant temperature to form an alginate mixed water material, the mass ratio of alginate to distilled water is 2-3:1, the temperature of the constant temperature stirring is 70-80°C, and the stirring speed is 200-400r / min; b2, the alginate mixed water material is quickly sheared and stirred, and dried at a constant temperature, and then ball milled to obtain alginate powder, the stirring of the shear stirring is 1000-2000r / min, the temperature of the constant temperature drying is 105-110°C, the ball milling pressure of the ball milling is 0.12-0.13MPa, and the temperature is 20-30°C. The fragmentation process utilizes constant temperature stirring to completely disperse water molecules into alginate to achieve the effect of dissolving. Due to the mass difference between water and alginate, alginate cannot be dissolved, but only forms an expansive dissolution. At the same time, high-speed shear stirring and ball milling stirring can form a gradient dispersion, and the constant temperature drying in the middle removes water molecules, thereby forming solid fragmentation in a dry environment, realizing the dispersion and subdivision of alginate.

[0017] Furthermore, the conductive carbon black in step 2 contains 12-15% by weight of graphene. Conductive carbon black has good electrical conductivity and can realize the transfer of electrons, but its heat transfer coefficient is similar to that of still air. It is a common thermal insulation material and is very likely to cause local temperature accumulation. To solve this problem, graphene is doped into the conductive carbon black, which can improve the thermal conductivity of the conductive carbon black and accelerate heat transfer. At the same time, graphene itself has a conductivity that is not inferior to that of conductive carbon black, and will not cause the conductivity of the conductive carbon black to decrease. The particle sizes of the graphene and conductive carbon black are both 10-50μm;

[0018] It can be seen from the above description that the present invention has the following advantages:

[0019] 1. The present invention solves the adhesion problem between the existing aluminum foil and the coating, and utilizes the rough structure of the aluminum foil surface in combination with the adhesive gel properties of sodium alginate to enhance the bonding strength between the coating and the aluminum foil, thereby ensuring the stability of the battery performance.

[0020] 2. The present invention uses sodium alginate as an adhesive to improve the bonding strength, and at the same time has the effect of adsorbing sodium ions, repelling anions in the electrolyte, and inhibiting interface side reactions. DETAILED DESCRIPTION

[0021] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.

[0022] Example 1

[0023] A method for preparing a carbon-coated aluminum foil for a sodium ion battery. The carbon-coated aluminum foil comprises an aluminum foil, a coating coated on the surface of the aluminum foil, and a sodium-based adhesive material located between the aluminum foil and the coating. The coating is a carbon black-based conductive coating, and the sodium-based adhesive material is sodium alginate.

[0024] Pre-treatment of raw materials before preparation:

[0025] The aluminum foil needs to be pre-treated before use, and the pre-treatment steps include: a1, soaking and cleaning the aluminum foil with an ethanol aqueous solution, and drying to obtain an aluminum foil with a clean surface, wherein the ethanol volume concentration of the ethanol aqueous solution is 40%, and the drying temperature is 80° C.; a2, rolling dilute hydrochloric acid and dilute alkali solution on the surface of the clean aluminum foil in sequence, rinsing and drying to obtain an aluminum foil with a slightly rough surface, wherein the pH of the dilute hydrochloric acid is 6-6.5, and the pH of the dilute alkali solution is 7.5-8;

[0026] The anhydrous ethanol is soaked in the vermiculite particles and stirred for 5 minutes before use, and then the vermiculite particles are used as filter materials for solid-liquid separation to obtain water-free ethanol. The stirring speed is 100 r / min, and the vermiculite particles are spherical particles with a particle size of 5 mm;

[0027] The alginic acid needs to be crushed before use, and the crushing step of the alginic acid includes: b1, adding alginic acid to distilled water and stirring at a constant temperature to form an alginate water mixture, the mass ratio of alginate to distilled water is 2:1, the temperature of the constant temperature stirring is 70°C, and the stirring speed is 200r / min; b2, the alginate water mixture is quickly sheared and stirred, and dried at a constant temperature, and then ball milled to obtain alginate powder, the stirring speed of the shearing stirring is 1000r / min, the temperature of the constant temperature drying is 105°C, the ball milling pressure of the ball milling stirring is 0.12MPa, and the temperature is 20°C;

[0028] The method for preparing the carbon-coated aluminum foil for sodium ion batteries comprises the following steps:

[0029] Step 1, dissolving sodium ethoxide and alginic acid in anhydrous ethanol, stirring and dispersing to form a suspension slurry; the mass ratio of sodium ethoxide to sodium alginate is 1:1.1, the concentration of alginic acid in anhydrous ethanol is 5g / L, and the stirring speed is 50r / min;

[0030] Step 2, adding a wetting dispersant to distilled water and stirring evenly until the wetting dispersant is completely dissolved in the distilled water, then adding conductive carbon black and continuing to stir to form a homogeneous conductive slurry, wherein the wetting dispersant adopts a BYK acrylate copolymer ammonium salt solution wetting dispersant, the concentration of the wetting dispersant in distilled water is 1g / L, the concentration of the conductive carbon black is 100g / L, the stirring speed is 100r / min, and the temperature is 20-30°C; the particle size of the conductive carbon black is between 10-50μm;

[0031] Step 3: Roll-coat the suspension slurry on the surface of the aluminum foil and dry it in a dry environment, then roll-coat the conductive slurry for a second time, let it stand and dry to obtain the coated aluminum foil. The roll-coating amount of the suspension slurry is 20 μL / m 2 The drying temperature is 70°C, and the secondary coating amount is 1g / m 2 , and place it in a static oven at 50°C;

[0032] Step 4, rolling the coated aluminum foil to obtain carbon-coated aluminum foil, wherein the pressure of the rolling treatment is 50T, the rolling speed is 20m / min, and the temperature is 80°C.

[0033] Example 2

[0034] A method for preparing a carbon-coated aluminum foil for a sodium ion battery. The carbon-coated aluminum foil comprises an aluminum foil, a coating coated on the surface of the aluminum foil, and a sodium-based adhesive material located between the aluminum foil and the coating. The coating is a carbon black-based conductive coating, and the sodium-based adhesive material is sodium alginate.

[0035] Pre-treatment of raw materials before preparation:

[0036] The aluminum foil needs to be pre-treated before use, and the pre-treatment steps include: a1, soaking and cleaning the aluminum foil with an ethanol aqueous solution, and drying to obtain an aluminum foil with a clean surface, wherein the ethanol volume concentration of the ethanol aqueous solution is 50%, and the drying temperature is 90° C.; a2, rolling dilute hydrochloric acid and dilute alkali solution on the surface of the clean aluminum foil in sequence, rinsing and drying to obtain an aluminum foil with a slightly rough surface, wherein the pH of the dilute hydrochloric acid is 6-6.5, and the pH of the dilute alkali solution is 7.5-8;

[0037] The anhydrous ethanol is soaked in the vermiculite particles and stirred for 10 minutes before use, and then the vermiculite particles are used as filter materials for solid-liquid separation to obtain water-free ethanol. The stirring speed is 200 r / min, and the vermiculite particles are spherical particles with a particle size of 10 mm;

[0038] The alginic acid needs to be crushed before use, and the crushing step of the alginic acid includes: b1, adding alginic acid to distilled water and stirring at a constant temperature to form an alginate water mixture, the mass ratio of alginate to distilled water is 3:1, the temperature of the constant temperature stirring is 80°C, and the stirring speed is 400r / min; b2, the alginate water mixture is quickly sheared and stirred, and dried at a constant temperature, and then ball milled to obtain alginate powder, the stirring of the shear stirring is 2000r / min, the temperature of the constant temperature drying is 110°C, the ball milling pressure of the ball milling is 0.13MPa, and the temperature is 30°C;

[0039] The method for preparing the carbon-coated aluminum foil for sodium ion batteries comprises the following steps:

[0040] Step 1, dissolving sodium ethoxide and alginic acid in anhydrous ethanol, stirring and dispersing to form a suspension slurry; the mass ratio of sodium ethoxide to sodium alginate is 1:1.3, the concentration of alginic acid in anhydrous ethanol is 5-10 g / L, and the stirring speed is 100 r / min;

[0041] Step 2, adding a wetting dispersant to distilled water and stirring evenly until the wetting dispersant is completely dissolved in the distilled water, then adding conductive carbon black and continuing to stir to form a homogeneous conductive slurry, wherein the wetting dispersant is a BYK acrylate copolymer ammonium salt solution wetting dispersant, the concentration of the wetting dispersant in distilled water is 2g / L, the concentration of the conductive carbon black is 400g / L, the stirring speed is 200r / min, and the temperature is 30°C; the particle size of the conductive carbon black is between 10-50μm;

[0042] Step 3: Roll-coat the suspension slurry on the surface of the aluminum foil and dry it in a dry environment, then roll-coat the conductive slurry for a second time, let it stand and dry to obtain the coated aluminum foil. The roll-coating amount of the suspension slurry is 50 μL / m 2 The drying temperature is 80°C, and the secondary coating amount is 2g / m 2 , and place it in a static oven at 70°C;

[0043] Step 4, rolling the coated aluminum foil to obtain carbon-coated aluminum foil, wherein the pressure of the rolling treatment is 70T, the rolling speed is 30m / min, and the temperature is 90°C.

[0044] Example 3

[0045] A method for preparing a carbon-coated aluminum foil for a sodium ion battery. The carbon-coated aluminum foil comprises an aluminum foil, a coating coated on the surface of the aluminum foil, and a sodium-based adhesive material located between the aluminum foil and the coating. The coating is a carbon black-based conductive coating, and the sodium-based adhesive material is sodium alginate.

[0046] Pre-treatment of raw materials before preparation:

[0047] The aluminum foil needs to be pre-treated before use, and the pre-treatment steps include: a1, soaking and cleaning the aluminum foil with an ethanol aqueous solution, and drying to obtain an aluminum foil with a clean surface, wherein the ethanol volume concentration of the ethanol aqueous solution is 45%, and the drying temperature is 85° C.; a2, rolling dilute hydrochloric acid and dilute alkali solution on the surface of the clean aluminum foil in sequence, rinsing and drying to obtain an aluminum foil with a slightly rough surface, wherein the pH of the dilute hydrochloric acid is 6-6.5, and the pH of the dilute alkali solution is 7.5-8;

[0048] The anhydrous ethanol is soaked in the vermiculite particles and stirred for 8 minutes before use, and then the vermiculite particles are used as filter materials for solid-liquid separation to obtain water-free ethanol. The stirring speed is 150r / min, and the vermiculite particles are spherical particles with a particle size of 8mm;

[0049] The alginic acid needs to be crushed before use, and the crushing step of the alginic acid includes: b1, adding alginic acid to distilled water and stirring at a constant temperature to form an alginate mixed water material, the mass ratio of alginate to distilled water is 3:1, the temperature of the constant temperature stirring is 75°C, and the stirring speed is 300r / min; b2, the alginate mixed water material is quickly sheared and stirred, and dried at a constant temperature, and then ball milled to obtain alginate powder, the stirring speed of the shearing stirring is 1500r / min, the temperature of the constant temperature drying is 105°C, the ball milling pressure of the ball milling stirring is 0.12MPa, and the temperature is 25°C;

[0050] The method for preparing the carbon-coated aluminum foil for sodium ion batteries comprises the following steps:

[0051] Step 1, dissolving sodium ethoxide and alginic acid in anhydrous ethanol, stirring and dispersing to form a suspension slurry; the mass ratio of sodium ethoxide to sodium alginate is 1:1.2, and the concentration of alginic acid in anhydrous ethanol is 5-10g / L, and the stirring speed is 80r / min;

[0052] Step 2, adding a wetting dispersant to distilled water and stirring evenly until the wetting dispersant is completely dissolved in the distilled water, then adding conductive carbon black and continuing to stir to form a homogeneous conductive slurry, wherein the wetting dispersant is a BYK acrylate copolymer ammonium salt solution wetting dispersant, the concentration of the wetting dispersant in distilled water is 2g / L, the concentration of the conductive carbon black is 300g / L, the stirring speed is 150r / min, and the temperature is 25°C; the particle size of the conductive carbon black is between 10-50μm;

[0053] Step 3: Roll-coat the suspension slurry on the surface of the aluminum foil and dry it in a dry environment, then roll-coat the conductive slurry for a second time, let it stand and dry to obtain the coated aluminum foil. The roll-coating amount of the suspension slurry is 20-50 μL / m 2 The drying temperature is 75°C, and the secondary coating amount is 2g / m 2 , and place it in a static oven at 60°C;

[0054] Step 4, rolling the coated aluminum foil to obtain carbon-coated aluminum foil, wherein the pressure of the rolling treatment is 60T, the rolling speed is 25m / min, and the temperature is 85°C.

[0055] Example 4

[0056] A method for preparing a carbon-coated aluminum foil for a sodium ion battery. The carbon-coated aluminum foil comprises an aluminum foil, a coating coated on the surface of the aluminum foil, and a sodium-based adhesive material located between the aluminum foil and the coating. The coating is a carbon black-based conductive coating, and the sodium-based adhesive material is sodium alginate.

[0057] Pre-treatment of raw materials before preparation:

[0058] The aluminum foil needs to be pre-treated before use, and the pre-treatment steps include: a1, soaking and cleaning the aluminum foil with an ethanol aqueous solution, and drying to obtain an aluminum foil with a clean surface, wherein the ethanol volume concentration of the ethanol aqueous solution is 45%, and the drying temperature is 85° C.; a2, rolling dilute hydrochloric acid and dilute alkali solution on the surface of the clean aluminum foil in sequence, rinsing and drying to obtain an aluminum foil with a slightly rough surface, wherein the pH of the dilute hydrochloric acid is 6-6.5, and the pH of the dilute alkali solution is 7.5-8;

[0059] The anhydrous ethanol is soaked in the vermiculite particles and stirred for 8 minutes before use, and then the vermiculite particles are used as filter materials for solid-liquid separation to obtain water-free ethanol. The stirring speed is 150r / min, and the vermiculite particles are spherical particles with a particle size of 7mm;

[0060] The alginic acid needs to be crushed before use, and the crushing step of the alginic acid includes: b1, adding alginic acid to distilled water and stirring at a constant temperature to form an alginate mixed water material, the mass ratio of alginate to distilled water is 3:1, the temperature of the constant temperature stirring is 75°C, and the stirring speed is 300r / min; b2, the alginate mixed water material is quickly sheared and stirred, and dried at a constant temperature, and then ball milled to obtain alginate powder, the stirring speed of the shearing stirring is 1500r / min, the temperature of the constant temperature drying is 105°C, the ball milling pressure of the ball milling stirring is 0.12MPa, and the temperature is 25°C;

[0061] The method for preparing the carbon-coated aluminum foil for sodium ion batteries comprises the following steps:

[0062] Step 1, dissolving sodium ethoxide and alginic acid in anhydrous ethanol, stirring and dispersing to form a suspension slurry; the mass ratio of sodium ethoxide to sodium alginate is 1:1.2, the concentration of alginic acid in anhydrous ethanol is 8 g / L, and the stirring speed is 60 r / min;

[0063] Step 2, adding a wetting dispersant to distilled water and stirring evenly until the wetting dispersant is completely dissolved in the distilled water, and then adding conductive carbon black and continuing to stir to form a homogeneous conductive slurry, wherein the wetting dispersant adopts a BYK acrylate copolymer ammonium salt solution wetting dispersant, the concentration of the wetting dispersant in distilled water is 2g / L, the concentration of the conductive carbon black is 300g / L, the stirring speed is 150r / min, and the temperature is 20-30°C; the conductive carbon black contains 15% by weight of graphene, and the particle sizes of the graphene and the conductive carbon black are both between 10-50μm;

[0064] Step 3: Roll-coat the suspension slurry on the surface of the aluminum foil and dry it in a dry environment, then roll-coat the conductive slurry for a second time, let it stand and dry to obtain the coated aluminum foil. The roll-coating amount of the suspension slurry is 40 μL / m 2 The drying temperature is 75°C, and the secondary coating amount is 2g / m 2 , and place it in a static oven at 60°C;

[0065] Step 4, rolling the coated aluminum foil to obtain carbon-coated aluminum foil, wherein the pressure of the rolling treatment is 60T, the rolling speed is 25m / min, and the temperature is 85°C.

[0066] Example 5

[0067] A method for preparing a carbon-coated aluminum foil for a sodium ion battery. The carbon-coated aluminum foil comprises an aluminum foil, a coating coated on the surface of the aluminum foil, and a sodium-based adhesive material located between the aluminum foil and the coating. The coating is a carbon black-based conductive coating, and the sodium-based adhesive material is sodium alginate.

[0068] Pre-treatment of raw materials before preparation:

[0069] The aluminum foil needs to be pre-treated before use, and the pre-treatment steps include: a1, soaking and cleaning the aluminum foil with an ethanol aqueous solution, and drying to obtain an aluminum foil with a clean surface, wherein the ethanol volume concentration of the ethanol aqueous solution is 45%, and the drying temperature is 85° C.; a2, rolling dilute hydrochloric acid and dilute alkali solution on the surface of the clean aluminum foil in sequence, rinsing and drying to obtain an aluminum foil with a slightly rough surface, wherein the pH of the dilute hydrochloric acid is 6-6.5, and the pH of the dilute alkali solution is 7.5-8;

[0070] The anhydrous ethanol is soaked in the vermiculite particles and stirred for 8 minutes before use, and then the vermiculite particles are used as filter materials for solid-liquid separation to obtain water-free ethanol. The stirring speed is 150r / min, and the vermiculite particles are spherical particles with a particle size of 8mm;

[0071] The alginic acid needs to be crushed before use, and the crushing step of the alginic acid includes: b1, adding alginic acid to distilled water and stirring at a constant temperature to form an alginate mixed water material, the mass ratio of alginate to distilled water is 3:1, the temperature of the constant temperature stirring is 75°C, and the stirring speed is 300r / min; b2, the alginate mixed water material is quickly sheared and stirred, and dried at a constant temperature, and then ball milled to obtain alginate powder, the stirring speed of the shearing stirring is 1500r / min, the temperature of the constant temperature drying is 110°C, the ball milling pressure of the ball milling stirring is 0.12MPa, and the temperature is 25°C;

[0072] The method for preparing the carbon-coated aluminum foil for sodium ion batteries comprises the following steps:

[0073] Step 1, dissolving sodium ethoxide and alginic acid in anhydrous ethanol, stirring and dispersing to form a suspension slurry; the mass ratio of sodium ethoxide to sodium alginate is 1:1.2, and the concentration of alginic acid in anhydrous ethanol is 5-10g / L, and the stirring speed is 80r / min;

[0074] Step 2, adding a wetting dispersant to distilled water and stirring evenly until the wetting dispersant is completely dissolved in the distilled water, and then adding conductive carbon black and continuing to stir to form a homogeneous conductive slurry, wherein the wetting dispersant adopts a BYK acrylate copolymer ammonium salt solution wetting dispersant, the concentration of the wetting dispersant in distilled water is 2g / L, the concentration of the conductive carbon black is 200g / L, the stirring speed is 150r / min, and the temperature is 20-30°C; the conductive carbon black contains 15% by weight of graphene, and the particle sizes of the graphene and the conductive carbon black are both between 10-50μm;

[0075] Step 3: Roll-coat the suspension slurry on the surface of the aluminum foil and dry it in a dry environment, then roll-coat the conductive slurry for a second time, let it stand and dry to obtain the coated aluminum foil. The roll-coating amount of the suspension slurry is 30 μL / m 2 The drying temperature is 75°C, and the secondary coating amount is 2g / m 2 , and place it in a static oven at 60°C;

[0076] Step 4, rolling the coated aluminum foil to obtain carbon-coated aluminum foil, wherein the pressure of the rolling treatment is 60T, the rolling speed is 25m / min, and the temperature is 85°C.

[0077] Comparative Example 1

[0078] Aluminum foil without conductive coating and surface roughening

[0079] Comparative Example 2

[0080] Rough aluminum foil without conductive coating.

[0081] The slurry of the hard carbon negative electrode material was coated on the negative electrode plates on the aluminum foil of Examples 1-3 and Comparative Examples 1-2, and the bonding force and impedance of the plates were tested. The results are as follows:

[0082]

[0083]

[0084] The above test surface shows that the carbon-coated aluminum foil prepared by the present invention not only has strong adhesion, but also can effectively reduce the electrode impedance.

[0085] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing a carbon-coated aluminum foil for a sodium ion battery, characterized in that: The carbon-coated aluminum foil comprises an aluminum foil, a coating coated on the surface of the aluminum foil, and a sodium-based adhesive material located between the aluminum foil and the coating; the coating is a carbon black conductive coating, and the sodium-based adhesive material is sodium alginate; The method for preparing the carbon-coated aluminum foil for sodium ion batteries comprises the following steps: Step 1, dissolving sodium ethoxide and alginic acid in anhydrous ethanol, and stirring and dispersing to form a suspension slurry; Step 2, adding a wetting and dispersing agent to distilled water and stirring evenly until the wetting and dispersing agent is completely dissolved in the distilled water, and then adding conductive carbon black and continuing to stir to form a homogeneous conductive slurry; Step 3, rolling the suspension slurry on the surface of the aluminum foil and drying it in a dry environment, then rolling the conductive slurry for a second time, standing and drying to obtain a coated aluminum foil; Step 4, rolling the coated aluminum foil to obtain carbon-coated aluminum foil.

2. The method for preparing a carbon-coated aluminum foil for a sodium ion battery according to claim 1, characterized in that: The mass ratio of sodium ethoxide to sodium alginate in step 1 is 1:1.1-1.3, the concentration of alginate in anhydrous ethanol is 5-10 g / L, and the stirring speed is 50-100 r / min.

3. The method for preparing the carbon-coated aluminum foil for sodium ion battery according to claim 1, characterized in that: The alginic acid is crushed before use.

4. The method for preparing the carbon-coated aluminum foil for sodium ion battery according to claim 1, characterized in that: The wetting and dispersing agent in step 2 is a BYK acrylate copolymer ammonium salt solution wetting and dispersing agent, and the concentration of the wetting and dispersing agent in distilled water is 1-2 g / L.

5. The method for preparing the carbon-coated aluminum foil for sodium ion battery according to claim 1, characterized in that: The concentration of the conductive carbon black in step 2 is 100-400 g / L, the stirring speed is 100-200 r / min, and the temperature is 20-30°C.

6. The method for preparing the carbon-coated aluminum foil for sodium ion battery according to claim 5, characterized in that: The conductive carbon black contains 12-15% by weight of graphene.

7. The method for preparing a carbon-coated aluminum foil for a sodium ion battery according to claim 1, characterized in that: The amount of suspension slurry rolled in step 3 is 20-50 μL / m 2 The drying temperature is 70-80°C, and the secondary coating amount is 1-2g / m 2 , and place it in a drying oven at 50-70℃.

8. The method for preparing the carbon-coated aluminum foil for sodium ion battery according to claim 1, characterized in that: The pressure of the rolling treatment in step 4 is 50-70T, the rolling speed is 20-30m / min, and the temperature is 80-90°C.

Citation Information

Patent Citations

  • Preparation method of carbon-coated foil for lithium ion battery

    CN113231278A

  • Negative pole piece of sodium ion battery, electrochemical device and electronic device

    CN113437254A